2022
DOI: 10.1007/s40487-022-00191-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Breast Cancer Management in Portugal: A Cross-Sectional Survey-Based Study of Medical Oncologists

Abstract: Introduction Cancer care providers have faced many challenges in delivering safe care for patients during the COVID-19 pandemic. This cross-sectional survey-based study investigated the impact of the pandemic on clinical practices of Portuguese medical oncologists caring for patients with breast cancer. Methods An anonymous online survey comprising 42 questions gathered information regarding COVID-19 testing, treatment in (neo)adjuvant and metastatic settings, and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“… New Zealand’s COVID-19 elimination pursuit helped minimize COVID-19 impact on breast cancer management. Alpuim Costa et al, Portugal 75 Cross-sectional survey-based study Dec 2020–Feb 2021 129 (NR) Impact of COVID-19 on clinical practices of oncologists for breast cancer patients. 71.3% of subjects reported reduced visits for new breast cancer cases, an increase in the tendency for telemedicine use, in cases of most aggressive indications such as HER2-positive, triple-negative, visceral crisis, clinical decision-making procedures remained unaffected, use of neoadjuvant therapy increased, but dose-dense regimens decreased, for less aggressive cases application of cycline-dependent kinase 4/6 inhibitor decreased, treatment with oral formulations and metronomic chemotherapy improved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… New Zealand’s COVID-19 elimination pursuit helped minimize COVID-19 impact on breast cancer management. Alpuim Costa et al, Portugal 75 Cross-sectional survey-based study Dec 2020–Feb 2021 129 (NR) Impact of COVID-19 on clinical practices of oncologists for breast cancer patients. 71.3% of subjects reported reduced visits for new breast cancer cases, an increase in the tendency for telemedicine use, in cases of most aggressive indications such as HER2-positive, triple-negative, visceral crisis, clinical decision-making procedures remained unaffected, use of neoadjuvant therapy increased, but dose-dense regimens decreased, for less aggressive cases application of cycline-dependent kinase 4/6 inhibitor decreased, treatment with oral formulations and metronomic chemotherapy improved.…”
Section: Resultsmentioning
confidence: 99%
“…Where possible, prescribing oral formulations was also proposed to limit attendance at hospitals with associated concerns with catching COVID-19 alongside increasing home delivery of medicines where possible. 75 The prescribing of metronomic chemotherapy, ie, frequent low doses of chemotherapy versus maximum dosing, may also be beneficial during a pandemic to limit the impact of chemotherapy on the immune system and patient recovery times ( Table 2 ). 75 , 76 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our respondents indicated that high-tech apps are able to increase subjects’ adaptability and protocol compliance in clinical research. Moreover, remote drug distribution and continuous medical oversight of adverse events in trials are available through telemedicine, which reduces hospital visits, decreases the risk of nosocomial infections and dropout rate ( 37 ), and eases the stress on medical resources. Although there are some limitations in telemedicine, such as the inability to collect bio-specimens, the difficulty in performing physical examination, and the poor quality of the internet provider network in low-income areas, it is still recommended as a routine element in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%